2022
DOI: 10.1002/jlb.5ma0422-505r
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic change of circulating innate and adaptive lymphocytes subtypes during a cascade of gastric lesions

Abstract: According to the Correa model, the intestinal‐type gastric cancer (GC) is preceded by premalignant lesions, including chronic gastritis, intestinal metaplasia and dysplasia. However, the dynamic change of innate and adaptive immune response during this process has not been studied comprehensively. In this study, we performed a comprehensive and trajectory analysis of circulating innate lymphoid cells (ILCs) and adaptive Th lymphocytes subtypes in patients spanning a cascade of gastric lesions. Increased circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Flow cytometry was performed using a FACSCanto instrument (BD Biosciences, San Jose, CA, USA) and analyzed using FlowJo software 10.8.1. The cell type annotation and gating strategy were performed as shown previously (27)(28)(29).…”
Section: Cell Isolation and Flow Cytometry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry was performed using a FACSCanto instrument (BD Biosciences, San Jose, CA, USA) and analyzed using FlowJo software 10.8.1. The cell type annotation and gating strategy were performed as shown previously (27)(28)(29).…”
Section: Cell Isolation and Flow Cytometry Analysismentioning
confidence: 99%
“…Individual immunity is coordinated across tissues, and the colonic antitumor immune response depends on continuous communication with the peripheral blood (25,26). Our previous study demonstrated peripheral adaptive and innate lymphocyte changes during human gastric cancer development (27). Considering the easily obtainable and non-invasive characteristics of peripheral blood samples, exploring changes in peripheral immune profiles is crucial and may help discover key functional cell subpopulations during CRC carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of ILC3s in gastric cancer is not well understood. Studies have shown that the levels of ILC3s and IL-22 in patients with gastritis, precancerous lesions, and gastric cancer are significantly higher than those in healthy populations, suggesting that ILC3s may play a role in gastric oncogenesis and have important immune functions [ 150 ]. Nevertheless, further high-quality studies are needed to deeply reveal and understand the relationship between ILC3s and gastric oncogenesis, especially regarding molecular mechanisms.…”
Section: Roles Of Ilc Subsets In Gastric Oncogenesismentioning
confidence: 99%
“…Elevated ILC3 and IL-22 levels in gastritis and gastric cancer patients (specific roles uncertain) [ 150 ]…”
Section: Figurementioning
confidence: 99%
“…According to the Correa model, the malignant development of normal gastric mucosa into gastric cancer is a long-term stage, especially in the three stages of “chronic atrophic gastritis - intestinal metaplasia - intraepithelial neoplasia” ( Correa, 1988 ). Therefore, three stages are termed gastric precancerous lesions (GPL), which are well-known risk factors for the development of intestinal-type gastric adenocarcinomas ( Fu et al, 2022 ). However, at present, there is no effective medicine for GPL treatment in modern medicine.…”
Section: Introductionmentioning
confidence: 99%